Tinjauan Regulasi Siber dan Kebijakan Keamanan Jaringan 5G: Perspektif Nasional dan Internasional - Fauzan Prasetyo Eka Putra; Dea Aulia Siswoyo; M. Idris Ainul Yaqin; Rica Oktavia (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2025)
This study discusses 5G network security regulations and policies from a national and international perspective, with a focus on the challenges and handling of global cyber threats. Given the cross-border threats, security and regulation are important issues in the implementation of 5G technology. The approach used is qualitative interpretive with additional limited experiments, including cyber attack simulations. The result of the study show that cyber policies in Indonesia are not yet fully coordinated, unlike countries such as the US, the European Union, and China which have more comprehensive regulations. Experiments prove that the implementation of protocols such as IPSec and TLS can reduce risks in 5G networks. Therefore, Indonesia is advised to form more integrated regulations that comply with international standards. This study also suggests further research in real scenarios and the development of a more in-depth policy evaluation system.